The biomarkers NSE and S100b have high predictive value regarding mortality in children resuscitated after cardiac arrest. (2nd May 2022) - Obling, L; Bangshoej, J; Liebetrau, B; Wiberg, S; Gjedsted, J; Kjaergaard, J; Hassager, C; Wanscher, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Children suffering from cardiac arrest (CA) have high mortality due to neurological injury and prognostication tools are sparse. The biomarkers neuron-specific enolase (NSE) and S100 calcium-binding protein b (S100b) are known to predict outcome in adult CA, but the use in children is not well investigated. Purpose: To assess the predictive value of the biomarkers NSE and S100b in children resuscitated from CA the first 72 hours following admission. Methods: In-hospital and out-of-hospital CA patients, age <18 and comatose at intensive care unit admission, were included consecutively at our hospital from 2011-2021 and analyses of NSE and S100b levels were made at three timepoints following admission: 12 to 24 hours, 24 to 48 hours and 48 to 72 hours. Patients were divided into groups of "survivors" and "non-survivors". The primary endpoint was 30-day mortality. Biomarker levels in the two groups were compared using the Mann-Whitney U test. Predictive value of NSE and S100b was determined by applying receiver operating characteristics (ROC) curves with area under the curves (AUC) presented for each timepoint. Results: We included 32 resuscitated patients with 12 (38%) patients dying within 30 days from resuscitation, i.e. 20 (62%) patients surviving. 14 patients were male sex and the median age was 15 years (6-16) in survivors. In non-survivors 8 patients were male sex and the median age was 7 years (2-15). Significantly higher levels of NSE and S100b were found in non-survivors compared to survivors at all timepoints following CA (Figure 1). For NSE the ROC curves obtained AUC values of 0.91 (0.75-1.0), 0.97 (0.92-1.0) and 0.98 (0.93-1.0) for prediction of 30-day mortality at the three timepoints. AUCs for S100b were 0.93 (0.84-1.0), 0.94 (0.86-1.0) and 0.94 (0.85-1.0), respectively. Conclusion: Levels of NSE and S100b in children resuscitated from CA are associated with 30-day mortality and both biomarkers appear to be strong predictors of mortality.